Vitamin D3 Nutritional Status Affects Gut Health of Salmonella-Challenged Laying Hens - Guo, Fangshen; Geng, Yanqiang; Abbas, Waseem; Zhen, Wenrui; Wang, Shuiqing; Huang, Yuechuan; Guo, Yuming; Ma, Qiugang; Wang, Zhong (Frontiers in Nutrition, 2022)
Salmonella enterica serovar Enteritidis (SE) is one of the most common pathogens associated with poultry health and foodborne Salmonellosis worldwide. The gut plays a pivotal role in inhibiting SE transintestinal transmission and contaminating poultry products. The nutritional status of vitamin D (VD) is involved in gut health apart from bone health. However, the impact of VD3 nutritional status on the gut health of Salmonella-challenged hens is rarely investigated. This study investigated the impact and possible mechanisms of VD3 nutritional status on the gut health of hens challenged with SE. Hens were fed basal diets with either 0 (deficient) or 3000 IU (sufficient) VD3/kg of diet, respectively. After 10 weeks of feeding, half of the hens were orally inoculated with either SE (1 × 109 CFU /bird). Results indicated that VD3 sufficiency reversed the disruptive effects on the laying performance of hens caused by Salmonella challenge or VD3 insufficiency by promoting VD3 metabolism. In addition, VD3 sufficiency ameliorated gut injury induced by either Salmonella or VD3 deficiency, shown by reducing Salmonella load and histopathological scores, suppressing TLR4-mediated inflammatory responses, and increasing expression of TJs along with decreasing pro-apoptotic protein expression and the number of TUNEL-positive cells in the jejunum. Besides, VD3 enriched the abundance of probiotics, such as Lactobacillus and Bacilli, and restored the balance of gut microflora. Collectively, dietary VD3 sufficient supplementation could alleviate Salmonella or VD3 deficiency-induced intestinal damage of hens via modulating intestinal immune, barrier function, apoptosis along with gut microbiota composition, revealing that VD3 could act as a novel nutritional strategy defending Salmonella invasion in hens.